Financial Instruments and Promotional Banking in the EU are Growing – But is this Justified? - Jorge Nú\~nez Ferrer (Intereconomics, 2018)
Institutions and the European Investment Bank are at the forefront of EU investment policy. Their role is expanding and it is now a widely-held position that an improvement in the economy will not eliminate the need for their intervention. The proposals for the 2021-2027 MFF launch more financial instruments and present 'InvestEU' as a larger more powerful version of the European Fund for Strategic Investments (EFSI). However, promotional banking is often misunderstood and so is the actual size of promotional banking in Europe in which InvestEU will operate.
Keywords: 330; EU budget; European Investment Bank; Institutional development; Multiannual Financial Framework